The Tricephalos in the Painted Dado of the Church of Nova Pavlica — Possible Origin of Iconography References - Gavrilović, Anđela Đ. (Actual Problems of Theory and History of Art, 2015)
The fantastic tricephalos in the painted dado of the sanctuary area of the church of the Presentation of the Virgin in Nova Pavlica, the endowment of Musić brothers, is depicted on the fresco layer dating before 1386. It is utterly unusual and interesting because of its iconography. It does not have any perfect analogy neither in Serbian monumental painting, nor in the Byzantine art in general. In previous literature it was referred to as “a fantastic animal”, “an apocalyptic, undefined, sea monster”, as “an Okeanos which is spitting water”. However, any further iconographical details of this fresco were not examined at all, which would be the aim of this paper. The appearance of the said tricephalos indicates that the origin of the various details of its iconography could be traced back to the ancient Greek and late antique art.